Human Papilloma Virus L1 Gene Methylation as a Potential Biomarker for Precancerous Cervical Lesion: a Preliminary Report - Suzanna P Mongan; Andrijono Andrijono; Hartono Tjahadi (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine whether HPV L1 gene methylation can be used in triage of precancerous cervical lesions. The main objective is to determine the genotype of HPV in cervical precancerous lesions and to determine the percentage, the sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratio of DNA HPV L1 methylation in precancerous cervical lesions. Methods: A number of 57 samples of paraffin blocks (FFPE) from precancerous lesions and cervical cancer biopsies in the Department of Pathology Faculty of Medicine-Cipto Mangunkusumo General Hospital that had been re-evaluated by the pathologist, underwent extraction of HPV DNA. The genotypes of HPV DNA were examined using primers GP5 / 6 and specific HPV 16, HPV 18 and HPV 52 probes and analyzed by real time PCR. Sequencing was performed on samples with unknown HPV DNA type that were detected using the specific probes to determine the type of HPV. Bisulfite conversion procedure was then performed for the samples that met the inclusion criteria. Results: There were 30 samples (52.6%) with CIN 1, 12 samples (21.1%) CIN 2, 9 samples (15.8%) CIN 3 and 6 samples (10.5%) of cervical cancer. Most of the samples were 36-45 years (35.1%). Of the total 57 samples, 55 samples were successfully extracted and determined the DNA genotyping of HPV (96.5%). HPV 16 infections both in the form of single or multiple was found to be 76.36%. The samples were mostly dominated by co-infection of HPV16 and 18 (49.1%) followed by HPV 16 (24.6%) and HPV 18 (14.0%). Based on the sequencing results there were other types of high risk HPV infection found: HPV 33, HPV 35, HPV 58 and also undeterminate risk HPV 53 and low risk HPV 54. After several procedures of optimization for methylation examination of HPV DNA L1 there was thin band found in electrophoresis procedure in 8 of 42 samples (19%) of HPV 16 after bisulfite conversion but once it was purified there weren’t any band found so we can not proceed to the stage sequencing. Until now we are still in the stage of optimizing the methylation procedure. Conclusion: HPV 16 infection were most commonly found in the form of single or multiple. Co-infection of HPV 16 and 18 were found in the majority of the samples. There were no significant correlation between HPV type and the severity of cervical lesions. Until now, the examination of DNA methylation HPV L1 already obtained eight samples of HPV 16 with a thin band on electrophoresis but the result could not be concluded because it is still in the process of optimization. [Indones J Obstet Gynecol 2017; 5-2: 120-126] Keywords: HPV DNA genotype, L1 gene methylation, precancerous cervical lesions